Effect of Light/Dark Cycle on Photosynthetic Pathway Switching and CO2 Absorption in Two Dendrobium Species - Cheng, Yongsan; He, Dongxian; He, Jie; Niu, Genhua; Gao, Rongfu (Frontiers in Plant Science, 2019)
Many Dendrobium species are both ornamental and medicinal plants in China. Several wild species have been exploited to near extinction, and facility cultivation has become an important way to meet the great market demand. Most Dendrobium species have evolved into crassulacean acid metabolism (CAM) pathways in adapting to harsh epiphytic environment, leading to low daily net CO2 absorption. Photosynthetic pathways of many facultative CAM plants are regulated by various environmental factors. Light/dark cycle plays an important role in regulating the photosynthetic pathway of several CAM species. The aims of this study were to investigate whether the photosynthetic pathway of Dendrobium species could be regulated between C3 and CAM by changing light/dark cycles and the daily net CO2 absorption could be enhanced by shortenting light/dark cycle. In this study, net CO2 exchange rates of D. officinale and D. primulinum were monitored continuously during two different light/dark cycles conversion compared to Kalanchoe daigremontiana as an obligate CAM plant. The net CO2 exchange pattern and stomatal behavior of D. officinale and D. primulinum were switched from CAM to C3-like by changing the light/dark cycle from 12 h/12 h to 4 h/4 h. However, this switching was not completely reversible. Compared to the original 12 h/12 h light/dark cycle, the dark, light, and daily net CO2 exchange amount of D. officinale were significantly increased after the light/dark cycle was changed from 4 h/4 h to 12 h/12 h, but those in D. primulinum was opposite and those in K. daigremontiana was not affected. Daily net CO2 exchange amount of D. officinale increased by 47% after the light/dark cycle was changed from 12 h/12 h to 4 h/4 h, due to the sharp increase of light net CO2 exchange amount. However, the large decrease of dark net CO2 exchange amount could not be offset by increased light net CO2 exchange amount, leading to reduced daily net CO2 exchange amount of D. primulinum. In conclusion, the 4 h/4 h light/dark cycle can induce the photosynthetic pathway of D. officinale and D. primulinum to C3-like, and improve the daily CO2 absorption of D. officinale.